O curso de especialização do Proeja no município de Sousa - PB: desafios e possibilidades na formação de educadores de EJA - Silva, Ana Paula Mendes (2011)
This work described a specific course of continued formation of educators of EJA carried through the Program of Integration of the Professional Education with the Basic Education in the modality of Young Education of e Adult - PROEJA in the city of Sousa, presenting the main characteristics of this course and as it was implanted in the Paraíba. For the realization of this study, it was adopted as methodological approach the documentary research, a time that, the survey of information was made through official and not official documents, beyond technique of interview half-structuralized with the general coordinator of the PROEJA, in the Paraíba and applied questionnaire the twenty pupils egresses of this course. Other data had been gotten, still, taking as base the story of personal experience, fruit of the intense participation and done comments still when pupil of the course. The research consisted of a case study and identified to challenges and possibilities lived deeply for the pupils in elapsing of the specialization course. We wait that the work can contribute for the field of the Professional Education and Adult the Young Education of e, in view of the reflection on one of the parts most important for the teaching: the formation.